GE_GERICHTE P/11382/2009 vom 27. Juni 2014 - GE Cour de justice (2014)
INFRACTIONS CONTRE L'HONNEUR; CALOMNIE; FIXATION DE LA PEINE; ATTÉNUATION DE LA PEINE | CP.174.1; CP.49.A.1; CP.48.1.C; CP.48.E; CP.178; CP.52; CP.34.1; CP.34.2; CPP.389; CPP.433.1.2